Assemblages of saproxylic beetles on large downed trunks of oak. Issue 6 (12th February 2016) - Milberg, Per; Bergman, Karl‐Olof; Sancak, Kerem; Jansson, Nicklas
Abstract: Old living oaks ( Quercus robur ) are known as a very species‐rich habitat for saproxylic beetles, but it is less clear to what extent such veteran trees differ from an even rarer feature: downed trunks of large oaks. In this study, we set out to sample this habitat, using window traps, with two aims: (1) to describe the variation of assemblages among downed trunks of different type and (2) to compare beetles on downed oaks with data from veteran standing trees. The results showed that trunk volume and sun exposure better explained assemblages as well as species numbers on downed trunks than did decay stage. Furthermore, species classified as facultative saproxylic species showed weak or no differentiation among downed trunks. Species with different feeding habits showed no apparent differentiation among downed trunks. Furthermore, species composition on dead, downed oak trunks differed sharply from that of living, veteran oaks. Wood or bark feeders were more common on veterans than downed trunks, but there was no difference for those species feeding on fungi or those feeding on insects and their remains. In conclusion, for a successful conservation of the saproxylic beetle fauna it is important to keep downed oak trunks, and particularly large ones, in forest and pastures as they constitute a saproxylic habitat that differs from that of living trees. Abstract : Richness of saproxylic beetles on downed oak trunks increases with size and sun exposure. Trunks differ in composition from living veteran oaks.